The prognostic value of miR-34 family in ovarian cancer: a systematic review and meta-analysis - Luo, Xiulan; Li, Xiaolu; Chen, Chaolin; Yang, Jing; Zheng, Hong (Frontiers in Oncology, 2025)
BackgroundThe aim of this study was to evaluate the association between miR-34 family expression and overall survival (OS) and progression-free survival (PFS) in women with ovarian cancer.MethodsLiterature searches were conducted using databases such as PubMed, Cochrane Library, EMBASE, Web of Science, Wanfang, and CNKI to identify studies reporting pooled hazard ratios (HRs) and 95% confidence intervals (CIs) examining the relationship between miR-34 family expression and overall survival (OS) or progression-free survival (PFS) in female patients with ovarian cancer. All potentially relevant studies were assessed and then pooled.ResultsThere were a total of seven literatures included in this systematic review and meta-analysis, which included 672 women. There was a significant improvement in survival for women with ovarian cancer when miR-34s expression was higher (OS, HR = 0.70, 95% CI:0.57–0.86; PFS, HR = 0.48, 95% CI:0.31–0.75). A subgroup analysis of miR-34 family members showed that differences between groups greatly affected PFS (HR = 0.50, 95% CI: 0.40–0.63).ConclusionBased on the results of this review, it appears that ovarian cancer women with high expression of miR-34s may have a better chance of surviving.Systematic Review Registration: PROSPERO (CRD42024499203).Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024499203.